PENULIS KITAB PEGON DI JAWA ABAD XX: BIOGRAFI KIAI ASRORI AHMAD DAN KARYA-KARYANYA - Jamaluddin Jamaluddin; Rahman Latif Alfian; Affaf Mujahidah; Kurnia Sari Wiwaha (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2022)
This article attempts to describe the biography of the prolific kiai writer and translator of the kitab Pegon, Kiai Asrori Ahmad who lived Wonosari, Magelang, Central Java in the twentieth century. The kiai, who was born in 1923, is widely known as a writer of numerous written books of Pegon, both in the form of translations and original ones. His work remarkably scattered in various Islamic disciplines, such as fiqh (Islamic jurisprudence), tawhid (monotheism), hadith, akhlaq-tasawwuf and sirah (history). In order to describe the biography of kiai Asrori comprehensively, this article uses the historical-codicological method by basing it on primary sources, such as interviews with kiai Asrori Ahmad's family and examining his works, as well as other supporting sources. Based on historical analysis. The result revealed that kiai Asrori Ahmad is a product of Islamic boarding school education who had the expertise of kitab kuning (yellow book). This special expertise was later developed by Kiai Asrori by improving it in within the tradition of the pesantren library, the book of pegon, under the guidance of Kiai Bisri Mustofa Rembang, one of the foremost preaching kiai and author of the twentieth century book of Pegon. Under the direction of his teacher who later became brother-in-law, Kiai Bisri Mustof, kiai Asrori eventually transformed into one among prolific writers of pegon book in the twentieth century. The record demonstrated approximately 30 titles spread out in 50 books that have been born from the patience and perseverance of Kiai Asrori Ahmad. All of his works were hatched from three important motivations: religious motivation, educational motivation and economic motivation.